Noble-metal-free and Pt nanoparticles-loaded, mesoporous oxides as efficient catalysts for CO2 hydrogenation and dry reforming with methane. (July 2019) - Sápi, András; Rajkumar, T.; Ábel, Marietta; Efremova, Anastasiia; Grósz, András; Gyuris, Anett; Ábrahámné, Kornélia B.; Szenti, Imre; Kiss, János; Varga, Tamás; Kukovecz, Ákos; Kónya, Zoltán
Graphical abstract: Highlights: Series of free-standing as well as controlled size Pt nanoparticles-loaded mesoporous metal oxides. Pt-free NiO exhibited the highest catalytic activity and showing 100% CH4 selectivity. Striking catalytic properties can be ascribed to the presence of metallic Ni and the optimal dynamics of Ni/NiOx structure. Abstract: In this study, a series of free-standing as well as controlled size Pt nanoparticles-loaded mesoporous metal oxides (NiO, Co3 O4, CeO2 and MnO2 ) with high surface area and designed pore structure were prepared by hard template method and used as catalysts for CO2 hydrogenation together with dry reforming of CO2 with methane. The physicochemical properties of catalysts were analysed by N2 adsorption-desorption isotherm, XRD, TEM, and H2 -TPR. Pt-free and Pt-loaded mesoporous NiO and Co3 O4 performed with high catalytic activity and selectivity for both CO2 activation reactions. Pt-free NiO exhibited the highest catalytic activity and also showing 100% CH4 selectivity between 473–673 K and ˜1:1 H2 /CO2 ratio between 673–973 K in CO2 hydrogenation and dry reforming with methane, respectively. The enhanced catalytic properties can be due to the existence of metallic Ni as well as the optimal dynamics of Ni/NiOx structure under reaction conditions.